CONSUMER PURCHASE BEHAVIOR ASSESSED FROM LIFESTYLE, SOCIAL, ECONOMIC ENVIRONMENT, CHARACTERISTICS (McDonald's Consumer Case Study Surakarta) - Ramlah, Ramlah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Research objectives: Knowing the lifestyle, socioeconomic environment, consumer characteristics simultaneously influence the purchasing decisions at McDonald's Restaurant, Surakarta. The method used in this research is descriptive quantitatively done to answer the research question that is analyzing the influence between variables. The population in this study was Mcdonald's buyers, the sample in this study amounted to 100 people . technical data analysis in this study using multiple regression equation model using SPSS program version 20.00.The results of this study prove that there is a significant influence simultaneously between lifestyle-free variables (X1) Socioeconomic Environment (X2) and Characteristics (X3) on variables tied to buyer behavior (Y) of 6.727% while persially showed that the influence of lifestyle variables (X1), social environment (X2) and characteristics (X3) on performance bound variables (Y) is X1. Keywords: environment, characteristics, consumer behavior.